164 ENGOT-cx11/GOG 3047/KEYNOTE-A18: a phase 3, randomized, double-blind study of pembrolizumab with chemoradiotherapy in patients with high-risk locally advanced cervical cancer. (13th November 2020) - Lorusso, D; Colombo, N; Coleman, R; Randall, L; Duska, L; Xiang, Y; Hasegawa, K; Nogueira-Rodrigues, A; Cibula, D; Raza Mirza, M; You, B; Oaknin, A; et al.
Abstract : Background: High-risk locally advanced cervical cancer (CC) has a poor prognosis, and >50% of patients recur in 2 years. Concurrent chemoradiotherapy (CRT) may enhance the immunostimulatory activity of the PD-1 inhibitor pembrolizumab. After KEYNOTE-158, in which pembrolizumab demonstrated durable antitumor activity, pembrolizumab monotherapy was approved for patients with PD-L1–positive recurrent or metastatic CC who progressed during or after chemotherapy. ENGOT-cx11/KEYNOTE-A18 (NCT04221945 ) is a phase 3, randomized, placebo-controlled study evaluating pembrolizumab with concurrent CRT in locally advanced CC. Trial design: Approximately 980 patients with high-risk, locally advanced, histologically confirmed CC who have not received systemic therapy, immunotherapy, definitive surgery, or radiation will be randomized 1:1 to receive 5 cycles of pembrolizumab 200 mg Q3W + CRT (5 cycles [with optional 6th cycle] of cisplatin 40 mg/m2 Q1W + external beam radiotherapy [EBRT] followed by brachytherapy) followed by 15 cycles of pembrolizumab 400 mg Q6W or 5 cycles of placebo Q3W + CRT followed by 15 cycles of placebo Q6W. Randomization is stratified by planned EBRT type, cancer stage at screening, and planned total radiotherapy dose. Treatment will continue until patient receives ≤20 cycles of pembrolizumab (5 cycles 200 mg Q3W, 15 cycles 400 mg Q6W) vs placebo ( 2 years) or until disease progression, unacceptable toxicity, or withdrawal. Primary endpoints are PFS per RECIST v1.1 by blinded independent central review and OS. Secondary endpoints include PFS at 2 years, OS at 3 years, complete response at 12 weeks, ORR, PFS and OS in PD-L1–positive patients, and safety. Enrollment is ongoing.